"I won't say I feel happy or sad" : experiences of siblings of young disabled people in disadvantaged socio-economic circumstances - Foote, Tamlyn Lou-Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
The impact of having a disabled sibling has been well researched in first world countries, revealing complex and varied results. However, in disadvantaged socioeconomic contexts, where disability has been found to be more prevalent, and where arguably, the functioning and quality of life of a disabled person is more likely to be affected by an impairment, very little is known about how siblings of young disabled people are affected. In response, this qualitative study explores the experiences of five, isiXhosa speaking adolescents, living in Joza Township, Grahamstown, who have a brother or sister with an intellectual, physical or developmental impairment. Semi-structured interviews were conducted and an interpretative phenomenological analytic approach was utilized to ascertain how the participants make sense of their worlds in relation to their sibling's disability. Specifically, this research aimed at developing an understanding of how the participants experienced their family climate, self-concept, interpersonal relations and daily living in relation to their disabled sibling. The results of this study reveal a prevailing sense of incongruity experienced by the participants, although there are variances between their experiences. While family climate was largely experienced as warm, the participants were ambivalent about their relationship with their mothers who are experienced more as providers than nurturers. The participants described oscillating between feelings of protectiveness and alliance, and responsibility and sacrifice toward their sibling. A high incidence of incongruity pertaining to their sense of self was noted; this was described as impacting on their interpersonal relations where an underlying sense of negative public perception in relation to the disability is perceived. Although the participants expressed feeling supported within their homes, it was evident that they experienced little support from peers or the community at large. Four out of the five participants did not report experiencing a sense of deprivation, despite their socio-economic contexts and described a day-to-day existence that allows for their needs to be met. This included adequate time during their day to pursue personal interests as opposed to their time being spent taking care of their disabled sibling or assisting their parents, who may be overburdened due to the added care and responsibilities a disabled child might require. Furthermore, it is suggested that the incongruity experienced by the participants could be the result of various factors including age, gender, birth order and the nature of their sibling's impairment. On the basis of the findings of this research, it can be concluded that the experiences of siblings of young, disabled people living in disadvantaged socioeconomic contexts cannot necessarily be described as being positive or negative, but are highly nuanced. In addition, the participants to some extent experience disability by association and are lacking in adequate support and opportunities to discuss their unique challenges. These insights serve to better inform disability studies in disadvantaged socio-economic circumstances. These findings are in accordance with earlier research.
Keywords: Mentally ill -- Family relationships; Mentally ill -- Care -- South Africa; Mentally ill children -- Care -- South Africa; Brothers and sisters of people with disabilities; Brothers and sisters of people with disabilities -- Psycnology; Brothers and sisters of people with disabilities -- Case studies -- South Africa -- Makhanda